The basic elements of the post keynesian analysis of the post-soviet model of Russian capitalism - Rozmainsky, I. (Економічний вісник Донбасу, 2016)
The paper tries to give Post Keynesian explanation of the most important problems of the Post-Soviet Russian Capitalism. The main idea is that institutions of this type of capitalism reduce uncertainty ineffectively. The main cause of it is a failure of the state as the effective enforcer of the contracts. In turn, higher uncertainty leads to chronic underinvestment, deindustrialization, technological degradation and tendency to sink into the underdevelopment trap. The accompanying phenomenon is the underdeveloped monetary system. All these factors contribute to the significant economic backwardness of the modern Russian economy. У статті зроблена спроба дати посткейнсіанське пояснення найбільш важливих проблем пострадянського російського капіталізму. Основна ідея полягає в тому, що інститути капіталізму такого типу неефективно зменшують невизначеність. Основною причиною цього є нездатність держави як ефективного виконавця контрактів. У свою чергу, більш висока невизначеність призводить до хронічного недофінансування, деіндустріалізації, технологічної деградації і схильності занурюватися в пастку відсталості. Супутнім явищем є недостатньо розвинена грошова система. Всі ці фактори сприяють значній економічній відсталості сучасної російської економіки. В статье сделана попытка дать посткейнсианское объяснение наиболее важных проблем постсоветского российского капитализма. Основная идея заключается в том, что институты капитализма такого типа неэффективно уменьшают неопределенность. Основной причиной этого является неспособность государства как эффективного исполнителя контрактов. В свою очередь, завышенная неопределенность приводит к хроническому недофинансированию, деиндустриализации, технологической деградации и склонности погружаться в ловушку отсталости. Сопутствующим явлением есть недостаточно развитая денежная система. Все эти факторы способствуют значительной экономической отсталости современной российской экономики.